Interactive Control of a Robotic Arm using Voice Recognition - K, Sika; A, Abinesh; N, Harideepan; K, Saravanan (Journal of Electronics and Informatics, 2024)
This research focuses on interactive control of a robotic arm using voice recognition, providing a user-friendly approach to controlling robotic systems through voice commands. The system is built on Arduino, integrating key components such as servo motors for precise movements, Bluetooth for wireless communication and motor drivers for higher torque applications. The HC-05 Bluetooth module supports voice recognition, enabling external devices to control the robotic arm through voice commands. This setup allows for quick responses and minimal human intervention. The proposed robotic arm supports actions such as pick and place, moving forward, backward, right, and left.
Keywords: Voice Recognition; HC-05 Bluetooth Module; Servo Motor; Robotic Arm; Arduino.